Clinical utility of plasma miR‐371a‐3p in germ cell tumors. Issue 2 (7th December 2018) - Mego, Michal; van Agthoven, Ton; Gronesova, Paulina; Chovanec, Michal; Miskovska, Vera; Mardiak, Jozef; Looijenga, Leendert H. J.
Abstract: Germ cell tumours predominantly of the testis ((T)GCTs) are remarkably chemotherapy sensitive. However, a small proportion of patients fail to be cured with cisplatin‐based combination chemotherapy. miR‐371a‐3p is a new liquid biopsy biomarker for (T)GCTs. The aim of this study was to evaluate clinical utility of plasma miR‐371a‐3p level in patients starting systemic chemotherapy. Patients were included before the first cycle (N = 180) and second cycle (N = 101) of systemic first line chemotherapy, treated between July 2010 and May 2017. Plasma miR‐371a‐3p levels were measured with the ampTSmiR test and compared to disease characteristics and outcome. Pretreatment plasma miR‐371a‐3p levels were increased in 51.7% of cases and associated with number of metastatic sites, presence of lung, retroperitoneal, and mediastinal lymph node metastases, S – stage, IGCCCG risk group, and response to therapy. Patients with a negative pretreatment plasma level had better progression‐free survival (PFS) and overall survival (OS) compared to patients being positive for miR‐371a‐3p (hazard ratio [HR] = 0.26, 95% confidence interval [CI] 0.09‐0.71, P = 0.02 for PFS and HR = 0.21, 95% CI 0.07‐0.67, P = 0.03 for OS, respectively). Patients negative for miR‐371a‐3p in both samples had a superior PFS (HR = 0.10, 95% CI 0.01‐21.49, P = 0.02) and OS (HR = 0.08, 95% CI 0.01‐27.81, P = 0.008) compared to patients with miR‐371a‐3p positive in both samples (multivariate analyses were non‐significant). In total 68% of the patients were S0. This study demonstrates clinical value of plasma miR‐371a‐3p level in chemotherapy naïve (T)GCT patients starting first line of chemotherapy to predict prognosis.